Andrianne Mini-Jupette Graft at the Time of Inflatable Penile Prosthesis Placement for the Management of Post-Prostatectomy Climacturia and Minimal Urinary Incontinence. Issue 5 (6th March 2018) - Yafi, Faysal A.; Andrianne, Robert; Alzweri, Laith; Brady, Jeffrey; Butcher, Michael; Chevalier, Daniel; DeLay, Kenneth J.; Faix, Antoine; Hatzichristodoulou, Georgios; Hellstrom, Wayne J.G.; Jenkins, Lawrence; Kohler, Tobias S.; et al.
Abstract: Background: After radical prostatectomy (RP), erectile dysfunction, often necessitating the need for inflatable penile prosthesis (IPP) insertion, and urinary incontinence and climacturia can ensue. Aim: To assess the efficacy and safety of the mini-jupette, a mesh used to approximate the medial aspects of the 2 corporotomies at the time of IPP insertion, for the management of climacturia and urine leakage in patients with minimal incontinence. Methods: We conducted a pilot multicenter study of patients with post-RP erectile dysfunction and climacturia and/or mild urinary incontinence (≤2 pads/day [ppd]) undergoing IPP insertion with concomitant placement of a mini-jupette graft. Outcomes: Pre- and postoperative erectile function, continence and climacturia, and overall surgical outcomes were assessed. Results: 38 patients underwent the mini-jupette procedure. The mean age of the population was 65.3 years (SD = 7.7). 30 had post-RP climacturia and 32 patients had post-RP incontinence (mean = 1.3 ppd, SD = 0.8). 31 patients received Coloplast Titan, 4 received AMS 700 LGX, and 3 received AMS 700 CX IPPs. Mean corporotomy size was 2.9 cm (SD = 1.0). Mean graft measurements were 3.2 cm (SD = 0.9) for width, 3.3 cm (SD = 1.3) for length, and 11.0 cm 2 (SD = 5.1) for surface area. At a mean follow-up of 5.1 months (SD = 6.9), there were 5 postoperative complications (13.2%) of which 4 required explantation. Climacturia and incontinence were subjectively improved in 92.8% and 85.7%, respectively. Mean ppd decreased by 1.3 postoperatively. Clinical Implications: The Andrianne mini-jupette is a feasible adjunct to IPP placement that can be used for subsets of patients with post-RP climacturia and/or minimal incontinence. Strengths and Limitations: Strengths of this study include the novel nature of this intervention, the multi-institutional nature of the study, and the promising results demonstrated. Limitations include the retrospective nature of the study and the heterogeneity of the techniques and grafts used by different surgeons involved. Conclusion: Longer follow-up and larger patient cohorts are needed to confirm the long-term safety and benefits of this intervention.